ANALISIS FAKTOR PENYEBAB RENDAHNYA KEMAMPUAN LITERASI (MEMBACA) SISWA KELAS V SD NEGERI REBAN DI ERA DIGITAL - Sriwahyuni, Indah; Wuryani, Meilan Tri; Kusumawati, Dian (Jurnal Gentala Pendidikan Dasar, 2026)
Reading literacy is a fundamental skill that plays a crucial role in supporting the learning success of elementary school students, particularly in the digital era. Although technological advances facilitate access to information, this does not always translate into increased interest and reading habits. This study examines the internal and external factors contributing to low reading literacy skills in students at Reban Public Elementary School and the relationship between digital media use and reading literacy skills. This study aims to analyze the factors contributing to low reading literacy skills in fifth-grade students at Reban Public Elementary School in the digital era. The study used a descriptive qualitative approach with a case study method. The subjects consisted of 10 fifth-grade students, one homeroom teacher, and parents. Data were collected through interviews, observation, and documentation, then analyzed using the Miles and Huberman model with source triangulation. The results indicate that students' reading skills are technically quite good, but their interest and reading habits are still low, and some students are not fluent in reading and understanding the content. Low reading literacy is influenced by internal factors (physiological conditions, motivation and interest in reading, habits, concentration) and external factors (family, teachers, and community) and reading literacy in the digital era.